2020
DOI: 10.1186/s12870-020-2245-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals the response mechanism of Cf-16-mediated resistance to Cladosporium fulvum infection in tomato

Abstract: Background: Leaf mold disease caused by Cladosporium fulvum is a serious threat affecting the global production of tomato. Cf genes are associated with leaf mold resistance, including Cf-16, which confers effective resistance to leaf mold in tomato. However, the molecular mechanism of the Cf-16-mediated resistance response is largely unknown. Results: We performed a comparative transcriptome analysis of C. fulvum-resistant (cv. Ontario7816) and C. fulvumsusceptible (cv. Moneymaker) tomato cultivars to identify… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 72 publications
1
20
1
1
Order By: Relevance
“…The rich-ratio in GO analysis is defined as amount of differentially expressed genes enriched in the pathway/amount of all genes in that pathway in the background gene set. The size of the dots represents the number of genes, and the color of the dots represents the false discovery rate (FDR) (Zhang et al 2020 ). KEGG analyses plots the number of genes belonging to enriched pathways.…”
Section: Methodsmentioning
confidence: 99%
“…The rich-ratio in GO analysis is defined as amount of differentially expressed genes enriched in the pathway/amount of all genes in that pathway in the background gene set. The size of the dots represents the number of genes, and the color of the dots represents the false discovery rate (FDR) (Zhang et al 2020 ). KEGG analyses plots the number of genes belonging to enriched pathways.…”
Section: Methodsmentioning
confidence: 99%
“…With the development of next-generation sequencing technology, research on the interaction between plants, insect vectors, and viruses has made rapidly progress ( Nouri et al, 2018 ). Transcriptome analysis revealed that defense-related pathways and oxidative stress in wheat were rapidly induced within hours after the initiation of aphid feeding, and that nicotinamide adenine dinucleotide phosphate (NADPH) oxidase plays an important role in aphid-induced defense responses and hydrogen peroxide (H 2 O 2) accumulation in wheat ( Zhang et al,2020a,b ). Many differentially expressed genes (DEGs) involved in photosynthesis, plant-pathogen interactions, secondary metabolism, and plant hormone signal transduction in watermelon response to Cucumber green mottle mosaic virus infection ( Sun et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…During long-term evolutionary interactions with plants, several pathogens successfully cause effectortriggered susceptibility response (ETS) by producing a number of effectors. Simultaneously, plants have evolved R genes that recognize these effectors and function through highly speci c interactions between effectors and their corresponding nucleotide-binding site and leucine-rich repeat (NB-LRR) class receptors [71]. In tomato, lncRNA23468 reportedly increases the expression of the NBS-LRR target genes (encoding R proteins), resulting in enhanced resistance to P.infestans [49].…”
Section: Discussionmentioning
confidence: 99%